2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23757
|View full text |Cite
|
Sign up to set email alerts
|

Creating Inclusive Environments in First-year Engineering Classes to Support Student Retention and Learning

Abstract: A new NSF-funded experimental study seeks to incorporate innovative curriculum activities that cultivate inclusive engineering identities and demonstrate how the engineering profession benefits from diversity. We intend to expand first-year engineering student perceptions about who can be an engineer and what engineers do. This effort aims to create a cultural shift in engineering departments so students think beyond stereotypical perceptions of who belongs to the engineering profession (White men) toward more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…One example is "'Findings suggest that the interactive theater sketch can help students work on teams more productively and demonstrate increasing value for diversity." (Paguyo, Atadero, Rambo-Hernandez, & Francis, 2015).…”
Section: Publication Implicationsmentioning
confidence: 99%
“…One example is "'Findings suggest that the interactive theater sketch can help students work on teams more productively and demonstrate increasing value for diversity." (Paguyo, Atadero, Rambo-Hernandez, & Francis, 2015).…”
Section: Publication Implicationsmentioning
confidence: 99%
“…These students also tend to face additional academic and social challenges during their transition to college when compared to their peers with parents who graduated from college 4,8,25 . The challenge in retaining firstgeneration and underrepresented minority students in engineering is often tied to a limited sense of belonging within engineering departments and a lack of "engineering identity" 16,17,22 . A student's sense of belonging can be defined as a psychological sense of identification and affiliation with the campus community 12 .…”
Section: Rationalementioning
confidence: 99%
“…Using literature review and observation of the subject courses in previous year, we identified a set of five potential activities that we detailed in 7 . We then worked closely with the course instructors of two different first-year courses, ENGR 101 Grand Challenges in Engineering and CIVE 102 Introduction to Civil and Environmental Engineering to implement several activities in each course.…”
Section: Description Of Intervention Activitiesmentioning
confidence: 99%